THE INFLUENCE OF LEADERSHIP, ORGANIZATIONAL CULTURE, MOTIVATION AND COMPENSATION ON EMPLOYEE PERFORMANCE IN REGIONAL APPARATUS ORGANIZATIONS (OPD) AT BAPERLITBANG KARIMUN REGENCY - Zulkifli Eko Purwanto; Bambang Satriawan; Ngaliman Ngaliman; Muammar Khaddafi (RADJA PUBLIKA, 2022)
Globalization is the tools of the growth of humans life on nowadays. As we know, it is not only controlled the human aspects, but it is also manage the humans activity as economy system. The economy system are controlled by the technology. These technology not only for manage the outcome or income of Indonesian people. But, it is also for the source of economy growth in humans life. The source of technology on nowadays are used is digital marketing. The words of digital marketing are taken from digital where its meant as technology and marketing as the economy of business of investor or the people. The purpose of this research aimed to know the effect of digital marketing towards the economy system. Further, the economy system on nowadays are not used the humans effort anymore. The methodology research that used on these research are used qualitative design. The design that applied on these research because the data and the sample of these research are based on the journals and the books quotation without any steps on analyze of the data. The steps of conducting the research are following; a) the formulation of topic, where it coming from the idea or the source of reading the books; b) data collection, after the topics are founded to be the topics of read, then the data are collecting of the theory, quotation or another aspect of economy or digital marketing from the journal or the books; c) the hypothesis determination, these steps are coming from the reading the book or the quotation; d) recycling the result, these steps is the main steps on the research to know the result of the idea or the things on the human’s aspect of the management economy system. After the result are founded, there were the result of these research as following : 1) the consideration of human’s effort being low; 2) the transaction of marketing being bigger; 3) improving the creativity of human skill.